2013
DOI: 10.1371/journal.pone.0072352
|View full text |Cite
|
Sign up to set email alerts
|

Geographical Analysis of the Distribution and Spread of Human Rabies in China from 2005 to 2011

Abstract: BackgroundRabies is a significant public health problem in China in that it records the second highest case incidence globally. Surveillance data on canine rabies in China is lacking and human rabies notifications can be a useful indicator of areas where animal and human rabies control could be integrated. Previous spatial epidemiological studies lacked adequate spatial resolution to inform targeted rabies control decisions. We aimed to describe the spatiotemporal distribution of human rabies and model its geo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 26 publications
1
45
0
1
Order By: Relevance
“…Of 10 patients, 6 were exposed in 5 countries (Thailand, Indonesia, Nepal, China, and India). Large numbers of human rabies cases among the local population are reported from these 5 countries, with the exception of Thailand (Technical Appendix), where only sporadic cases of rabies in humans are now reported ( 1 , 17 25 ; J.M. Shresta, 2012, pers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of 10 patients, 6 were exposed in 5 countries (Thailand, Indonesia, Nepal, China, and India). Large numbers of human rabies cases among the local population are reported from these 5 countries, with the exception of Thailand (Technical Appendix), where only sporadic cases of rabies in humans are now reported ( 1 , 17 25 ; J.M. Shresta, 2012, pers.…”
Section: Discussionmentioning
confidence: 99%
“…In Thailand, rabies cases in humans show no specific geographic distribution. In Indonesia and Nepal, cases are concentrated in specific areas ( 1 , 17 25 ; P. Rupali, 2012, pers. comm.).…”
Section: Discussionmentioning
confidence: 99%
“…2). Village selection was also based on existing reports that these are important endemic foci for rabies in China [3] and on the suggestion from the officers of Longlin animal husbandry and veterinary bureau that these could represent typical rural communities.
Fig. 2Map of the study area
…”
Section: Methodsmentioning
confidence: 99%
“…Currently in China, rabies ranks third in the list of 39 infectious diseases of mandatory notification in both 2012 and 2013 [2]. Recent studies have demonstrated that most rabies cases cluster in the provinces of the south of China [3] with reports indication a reemergence in Guangxi province [4]. …”
Section: Backgroudmentioning
confidence: 99%
“…Spatial analysis was performed in the AL cases dataset to find clusters according to their location using the Density-Based Spatial Clustering of Applications with Noise (DB-SCAN) [16][17][18] algorithm on R statistical software 19,20 using the flexible procedures for clustering package 21 . This algorithm identifies clusters by finding point subsets, which have a minimum number of points that are density-connected from each point's neighborhood within a given radius.…”
Section: Spatial Data Analysismentioning
confidence: 99%